Find the Taylor series solution of following
(X2+1)y''+4xy'+(x-5)y=0 y(2)=-1
y'(2)=3
Solution;
By definition, Taylor's series expansion of f(x) at x=a is given by;
"f(x)=f(a)+f'(a)(x-a)+\\frac{f"(a)}{2!}(x-a)^2+\\frac{f'''(a)}{3!}(x-a)^3+..."
We are given X=2,hence;
"f(x)=f(2)+f'(2)(x-2)+\\frac{f''(2)}{2!}(x-2)^2+\\frac{f'''(2)}{3!}(x-2)^3+..."
Since we have;
y(2)=-1
y'(2)=3
Also;
(x2+1)y''+4xy'+(x-5)y=0
By substitution;
(22+1)y''+4(2)(3)+(2-5)(-1)=0
5y''=-27
y''(2)="\\frac{-27}{5}"
Now ,find the triple derivative at x=2;
(x2+1)y''+4xy'+(x-5)y=0
Distribute;
"x^2\\frac{d^2y}{dx}+\\frac{d^2y}{dx^2}+4x\\frac{dy}{dx}+xy-5y=0"
Differentiate;
"[x^2\\frac{d^3y}{dx^3}+\\frac{d^2y}{dx^2}2x]+\\frac{d^3y}{dx^3}+[4x\\frac{d^2y}{dx^2}+4\\frac{dy}{dx}]+[x\\frac{dy}{dx}+y]-0=0"
Rewrite as;
"[x^2y'''+2xy'']+y'''+[4xy''+4y']+[xy'+y]=0"
Substitute all known values;
"4y'''-\\frac{27}{5}(4)+y'''-\\frac{27}{5}(8)+4(3)+2(3)-1=0"
Simplify;
"5y'''-\\frac{324}{5}+17=0"
Equate to obtain;
y'''(2)="\\frac{239}{25}"
Hence;
"f(x)=-1+3(x-2)-\\frac{27}{10}(x-2)^2+\\frac{239}{150}(x-2)^3+..."
Distribute;"f(x)=-1+3(x-2)-\\frac{27}{10}(x^2-4x+4)+\\frac{239}{150}(x^3-6x^2+12x-8)+..."
Simplify;
"f(x)=-\\frac{2291}{75}+\\frac{823}{25}x-\\frac{613}{50}x^2+\\frac{239}{150}x^3+..."
Comments
Leave a comment